Efficacy of combined hormonal vaginal ring in comparison to combined hormonal pills in heavy menstrual bleeding. (August 2016) - Dahiya, Pushpa; Dalal, Monika; Yadav, Anu; Dahiya, Krishna; Jain, Shaveta; Silan, Vijay
Abstract: Objective: To compare the efficacy, acceptability and compliance of combined hormonal vaginal ring (CVR), with combined hormonal pills (CHP) in patients with heavy menstrual bleeding (HMB). Study design: This prospective study was conducted in 50 women with HMB in age group of 25–40 years. Patients were divided in two groups of 25 each and followed for six treatment cycles. In each group, cycle comprised of three weeks of CVR (releases 15 μg of EE and 120 μg of the etonogestrel per day) or CHP (containing 30 μgm of EE and 150 μgm of LNG) use, followed by one ring or pill free week. After each cycle, patients were evaluated about the amount of blood loss and duration of bleeding by the pictoral blood assessment chart (PBAC), early bleeding (EWB), continued bleeding (CWB), intermenstrual bleeding, intended bleeding, compliance, and user acceptability. The collected data were analyzed using the Chi square test, t -test and ANOVA test. Result: Reduction in PBAC score for CVR (70.73%) and CHP group (70.02%), duration of bleeding and incidence of EWB was comparable among the two groups. The incidence of intermenstrual bleeding was lower in CVR than in CHP group in cycle 3 and 4 with significant p value. The incidence of CWB was significantly lower and the incidence of intended bleeding pattern in CVR group was significantly higher in cycle 3, 4, 5 and 6, signifying better cycle control. Compliance was also higher in CVR (88%) than CHC (75.33% of all cycles). Conclusion: This trial suggests that both the CVR and CHP are very effective short-term treatments for HMB in reproductive age group. However, women had better cycle control and compliance with CVR. This may be an attractive option among the wide variety of medications used to treat HMB.